Study on the interaction of taiwaniaquinoids with FTO by spectroscopy and molecular modeling. Issue 14 (26th October 2017) - Ren, Ting; Zhang, Lijiao; Wang, Jinqian; Song, Chuanjun; Wang, Ruiyong; Chang, Junbiao
Abstract : In this work, an attempt has been made to study the interaction of four taiwaniaquinoids with fat mass and obesity-associated protein (FTO) by UV–vis absorption, fluorescence spectroscopy, and molecular docking techniques. The results indicated that taiwaniaquinoids effectively quenched the intrinsic fluorescence of FTO via static quenching. According to the binding constants and thermodynamic parameters at three different temperatures, the hydrophobic force and electrostatic interactions appeared be the predominant intermolecular forces in stabilizing the complex. Results revealed that W-4 was the strongest quencher and W-3 was the weakest. The results of synchronous and three-dimensional fluorescence spectra showed that the conformation of FTO was changed. In addition, the influence of molecular structure on the quenching effect has been investigated.